PENGGUNAAN MEDIA AJAR SCRAMBLE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS 1 SEKOLAH DASAR - Sely Amelia (STKIP Subang, 2023)
Reading ability is a crucial aspect of language proficiency. This is because reading ability can influence learning outcomes and processes. Based on observations conducted in class 1 of SDN 195 Isola, it was found that students had below-average learning outcomes. The cause was identified as the students' insufficient reading ability, which affected their learning outcomes. Therefore, the researcher developed an instructional media using the scramble method to enhance early reading skills. The research employed a classroom action research design to examine the impact of using the scramble media on improving the early reading ability and learning outcomes of grade 1 students at SDN 195 Isola. The research subjects consisted of 26 students. The study followed several procedures, including planning, implementation, observation, and reflection. The success indicator of this research was the improvement in students' learning outcomes based on their reading ability. The research instruments used were observation sheets and learning outcome tests. The results of the study indicated that the scramble media could enhance early reading ability and improve students' learning outcomes. The improvement in learning outcomes was measured based on the pre-cycle, cycle I, and cycle II results. The test results showed a 22% increase in learning outcomes between the pre-cycle test and the evaluation in cycle II. Therefore, it can be concluded that the use of the scramble media can enhance the early reading ability of grade 1 students in elementary school.